LINGUISTIC INTERPRETATION OF EUPHEMISMS USING FOLK PROVERBS - Yuldashevna, Ibragimova Zamira (PT. Antis International Publisher, 2024)
This article focuses on the linguistic and cultural significance of euphemisms used in folk proverbs and the etymology of their origin